Effectiveness of dolutegravir-based vs boosted darunavir-based first-line 3-drug regimens in people with HIV with advanced disease: A trial emulation - Roberta Gagliardini; Andrea Giacomelli; Cristina Mussini; Stephen R. Cole; Jessie K. Edwards; Carmela Pinnetti; Alessandro Raimondi; Spinello Antinori; Silvia Nozza; Valentina Mazzotta; Giulia Carla Marchetti; Sergio Lo Caputo; et al. (International Journal of Infectious Diseases)
Background: No randomized comparisons exist between dolutegravir (DTG) and boosted-darunavir (DRV/b) for people initiating treatment with advanced HIV. Methods: Antiretroviral therapy (ART)-naïve people with HIV (PWH) with CD4 < 200 cells/mm3 or AIDS who started a first-line three-drug regimen with DTG or DRV/b were included. The primary outcome was a composite endpoint of newly diagnosed AIDS, serious non-AIDS events (SNAE), death, virological failure (VF), or discontinuation of the anchor drug due to failure or toxicity. A marginal structural Cox regression model was used to estimate the effect of starting DTG vs DRV/b-based regimens. Results: A total of 1323 advanced ART-naïve PWH were included, 895 starting DTG and 428 DRV/b. The unweighted risks of the composite endpoint by 48 months were 21.1% (95% CI: 18.1; 24.1%) for DTG vs 37.9% (95% CI: 32.7; 43.2%) for DRV/b (P < 0.001). First-line treatment with DTG showed a lower risk of experiencing the composite endpoint than DRV/b (wHR of DTG vs DRV/b 0.47, 95% CI: 0.35; 0.64, P < 0.001). Conclusion: Under the stated assumptions, this analysis indicates that in ART-naïve PWH with advanced disease, ART initiation with DTG vs DRV/b-based regimens leads to a 50% reduction in the risk of AIDS/SNAE/death/VF/discontinuation. This observed difference is partly explained by discontinuation of the anchor drug.